Interaction of acridine-calix[4]arene with DNA at the electrified liquid|liquid interface - Kivlehan, F.; Lefoix, M.; Moynihan, H.; Thompson, D.; Ogurtsov, V.; Herzog, G.; Arrigan, Damien (Pergamon-Elsevier Science Ltd, 2010)
The behaviour of an acridine-functionalised calix[4]arene at the interface between two immiscible electrolyte solutions (ITIES) is reported. Molecular modelling showed that the acridine-calix[4]arene has regions of significant net positive charge spread throughout the protonated acridine moieties, consistent with it being able to function as an anion ionophore. The presence of this compound in the organic phase facilitated the transfer of aqueous phase electrolyte ions. Upon addition of double stranded DNA to the aqueous phase, the transfer of electrolyte anions was diminished, due to DNA binding to the acridine moiety at the ITIES. The behaviour provides a basis for DNA hybridization detection using electrochemistry at the ITIES.